BELAJAR DAN MENGAJAR PERSPEKTIF ISLAM - As'ad As'ad (Universitas Islam Negeri Sumatera Utara Medan, 2019)
Learning activity is an interesting because as individual and social creatures, humans always try to know something that is in their environment to show their human existence. Learning means trying to know something, trying to gain knowledge (intelligence, skills). And teaching is giving and explaining to others about a science. teaching and learning is an activity that is done in order to gain knowledge, whereas in the process itself there are students who receive knowledge and there are educators who give lessons. Students also have an important role in this process. Between learning, teaching and students have a very relationship.Kata Kunci : Belajar, Mengajar, dan Perspektif Islam